2019
DOI: 10.5812/jjm.94171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nested-PCR and Loop-Mediated Isothermal Amplification for Cutaneous Leishmaniasis Diagnosis

Abstract: Background: Leishmaniasis is a protozoan disease caused by Leishmania genus and its most common form is cutaneous leishmaniasis. The number of reported cases of cutaneous leishmaniasis in Khuzestan, southwest Iran, continues to increase. Therefore, early, accurate diagnosis is crucial for successful therapy. Objectives: The Nested PCR is a molecular method with high sensitivity and specificity in detecting leishmaniasis, but this method requires advanced equipment and skilled labor. Therefore, developing a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In Eastern Mediterranean countries where Cutaneous Leishmaniasis is endemic, the standard laboratory test involves light microscopy examination of a smear prepared by scraping a suspected lesion. This method enables the visual identification of parasites following Giemsa stain colouration [ 7 ]. Ideally, results are obtained in approximately one and a half hours when colouration and microscopy readings are performed directly [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eastern Mediterranean countries where Cutaneous Leishmaniasis is endemic, the standard laboratory test involves light microscopy examination of a smear prepared by scraping a suspected lesion. This method enables the visual identification of parasites following Giemsa stain colouration [ 7 ]. Ideally, results are obtained in approximately one and a half hours when colouration and microscopy readings are performed directly [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CL-RDT received notable acceptance for its user-friendliness and time efficiency compared to traditional microscopy. Micro-costing data revealed that the average unit cost for microscopy is 15 MAD [ 7 31 ], whereas 75 MAD [52–131] for CL-RDT. Altogether, the diagnostic cost for microscopy is 115 MAD±4, marginally higher than the 102 MAD±2 for CL-RDT (p = 0,05).…”
mentioning
confidence: 99%
“…Although some leishmaniasis types, such as mucocutaneous and visceral leishmaniasis, may cause severe health issues and death, cutaneous leishmaniasis is typically not life threatening and can heal independently in many cases [ 25 , 26 ]. For Leishmania detection, LAMP is a widely used isothermal amplification method and has been reported to show similar results to nested PCR [ 27 ]. Sereno et al have reviewed more isothermal amplification methods in parasites of the Trypanosomatidae family, such as NASBA, LAMP, RPA, and PSR, in which RPA and LAMP rank highly in terms of field applicability [ 28 ].…”
Section: Introductionmentioning
confidence: 99%